Distribution of shallow water soft and hard bottom seabeds in the Isla del Coco National Park, Pacific Costa Rica - Sibaja Cordero, Jeffrey Alejandro (2012)
Geographic Information Systems (GIS) applications used in marine habitats are powerful tools for management and monitoring of marine reserves and resources. Here, we present a series of maps of the soft and hard substrates in the shallow waters (>80 m depth) of Parque Nacional Isla del Coco (PNIC= Isla del Coco National Park). We use bathymetry data and field data as input for a GIS, GAM, and kriging methods to generate a series of maps that describe the bottom characteristics. Eight types of bottom were found in the PNIC by composition and grain size. The shore of the island and islets consisted of rocky formations (mainly basalts), with coral reefs in the subtidal of some areas. Rhodolith beds had a dispersing distribution. The bottom on the southern and southwestern region is hard substrate, while sediments cover the northern and northeastern zones. Slightly gravelly sand dominated the bays, while gravelly sand (with more coarse grains) was frequent offshore. The inner areas of Chatham and Wafer bays have mud and organic matter. The sediments in the area are mostly carbonates, except in Bahía Yglesias where clastic sediments (from the erosion of basalts) are pre-sented. The information generated in this study could be a valuable input for future monitoring in the PNIC.